Technical Adequacy of the Social, Academic, and Emotional Behavior Risk Screener in an Elementary Sample. (December 2016) - Kilgus, Stephen P.; Sims, Wesley A.; von der Embse, Nathaniel P.; Taylor, Crystal N.
The purpose of this study was to evaluate the psychometric defensibility of the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS): a quick and easy universal screener for behavioral and emotional risk. Elementary school teachers completed the SAEBRS with 346 students in Grades 3 to 5. Teachers also completed two criterion measures, including the Student Risk Screening Scale (SRSS) and the Student Internalizing Behavior Screener (SIBS). Additional extant behavioral and academic data sources were collected including office discipline referrals, suspensions, curriculum-based measurement scores, and statewide achievement test scores. Reliability analyses were indicative of the internal consistency of all four SAEBRS scales, whereas correlational analyses and Mann–Whitney–Wilcoxon tests supported the criterion-related and construct validity. Receiver operating characteristic curve analyses suggested each SAEBRS scale was associated with acceptable or optimal diagnostic accuracy. However, cut scores selected as most appropriate within each SAEBRS scale were found to differ from those identified in previous studies, potentially suggesting the influence of criterion outcome under consideration on SAEBRS diagnostic accuracy. Limitations and future directions for research are discussed, with emphasis on the need for continued examination of the extent of variability in SAEBRS cut score performance.